Effect of attachment style on selective attention in panic disorder - Klipsch, Ottilia; Schauenburg, Henning; Nikendei, Christoph; Benecke, Cord; Dinger, Ulrike (Journal of social and clinical psychology, 2020)
Introduction: Given the heterogeneity of results in the attentional bias to threatening information in patients with panic disorder, we investigated the attentional bias toward threat and the moderating effect of attachment styles in a female-only sample of panic patients and a nonclinical control group.Methods: Female panic patients (n = 47) were compared to a female control group (n = 47) using a modified Dot Probe Task with body-related and interpersonal threat as well as attachment positive words.Results: An attentional bias toward threat words was not replicated. Furthermore, there was no moderation effect on attentional bias by attachment styles. However, high attachment avoidance was associated with faster reaction times (RT) in attachment positive compared to attachment threat trials in both groups. In the patient group, attachment anxiety was associated with faster RT in panic threat trials compared to attachment positive trials. Anxiously attached controls reacted faster to attachment positive vs. attachment threat trials.Discussion: No attentional bias was found in the present study. However, the findings suggest that attachment avoidance and attachment anxiety differently influence attention responses to trials that include different emotional stimuli in clinical and nonclinical, female participants. Attachment insecurity may modify attention when processing trials including both, threat and positive stimuli.
Gesehen am 14.10.2020